WIKAMA: A Web-Based Tourism Information System for Maros Regency Using the Waterfall Method - Paula Vebrianti Kewa Payon Riantobi; Nurhalisa; Muh. Kahlil Gibran; Ahmad Khairul Shiddiq; Muhammad Nur Faiz (Academic Bright Collaboration, 2025)
The Web-Based Tourism Information System of Maros Regency (WIKAMA) was developed to provide an efficient platform for promoting tourist destinations and delivering accessible visitor information. The system enhances the tourism experience by offering real-time details on attractions, facilities, and services. Development followed the Waterfall methodology, incorporating modules for destination management, gallery updates, and user interaction. Evaluation employed both functional and non-functional testing to assess performance, security, and usability. Black Box testing confirmed that all seven core functionalities operated successfully and complied fully with the specified requirements. While the system has met its initial objectives, further enhancements are recommended, including online ticketing, integration with social media for broader outreach, and optimization for improved performance. These improvements are expected to strengthen WIKAMA’s role as a digital tool for tourism promotion and regional economic development in Maros Regency.